Tractor Transport in the Soviet Arctic - Urvantsev, N. (Polar Record, 1936)
Mechanical transport was first used by the author of this article at the time of the investigation of the Norilsk mining field (Lat. 69° 20′ N., Long. 88° 8′ E.) in 1925 for the purpose of taking goods from the port of unloading to the village of Dudinsk on the River Yenisei over a distance of 85 km. across tundra. At that time the tractor industry had only just come into being in the Soviet. Special machines for cross-country freight did not exist, so imported caterpillar tractors of the Reno make were used, drawing sledges freighted up to five tons. Certain constructional defects in the machines, and particularly in the sledges, as well as lack of experience in the work, combined to make the results far from satisfactory at this stage. At the end of the winter we had only succeeded in making one full journey and had transported only ten tons of profitable cargo on three machines. Nevertheless, this first experiment was valuable in that it demonstrated that, given mechanical improvement, the tractors might revolutionise polar transport. In this case, for instance, three machines had transported rapidly a cargo which would have required a caravan of two hundred and forty reindeer. It was ascertained also by this trial that caterpillar tractors of this type were suitable only for work in the vicinity of a base on smooth and hard roads. For transport over long distances in new and soft snow they were less satisfactory.